The european cycle route network Eurovelo. Challenges and opportunities for sustainable tourism. Study. - (:unkn) unknown (My University, 2009)
The study evaluates the challenges and opportunities of developing a cycle tourism network across Europe. It focuses on EuroVelo, a network of 12 long-distance routes. The study reviews the market for cycle tourism in Europe and presents a EuroVelo demand model. It also reviews the carriage of cycles on trains. Finally,it evaluates the potenzial of the Iron Curtain Trial.
Keywords: Individualverkehr; Fahrradverkehr; Radwegenetz; Fahrradweg; Fahrradförderung; EU-Politik; Radverkehrsförderung; Fahrradinfrastruktur; Fahrradtourismus; Fahrradmitnahme; Potenzialanalyse; Handlungsempfehlung